Changing Patterns of Undiagnosed HIV Infection in the Netherlands: Who Benefits Most from Intensified HIV Test and Treat Policies? - Eline L M Op de Coul; Imke Schreuder; Stefano Conti; Ard van Sighem; Maria Xiridou; Maaike G Van Veen; Janneke C M Heijne (PLoS ONE, 2015)
To estimate HIV prevalence, the number of people living with HIV/AIDS (PLWHA) and the undiagnosed proportion in the Netherlands for 2012, and to compare these with published 2007 estimates.Synthesis of all available data sources.Multi-Parameter Evidence Synthesis (MPES) was used to obtain estimates in mutually exclusive key populations at higher risk in three geographical regions (Amsterdam, Rotterdam, rest of the Netherlands). Data sources included HIV prevalence surveys, diagnoses at STI clinics, and registered cases in HIV care. Group specific estimates were reported as Bayesian posterior medians and 95% credible intervals (CrI).The 2012 model estimated 24,350 PLWHA (95% CrI 20,420-31,280) aged 15-70 years; 2,906 (+14%) more than in 2007. The estimated population HIV prevalence was 0.20% (95% CrI 0.17-0.26%). The overall proportion of undiagnosed HIV was lower in 2012 (34%, 95% CrI 22-49%) compared to 2007 (40%, 95% CrI 25-55%). After MSM, migrants from sub-Saharan Africa and the Caribbean formed the largest groups of PLWHA, but proportions of undiagnosed HIV remained high in these groups, 48% and 44% respectively. Amsterdam had lowest proportions undiagnosed for most key populations at higher risk, including MSM and migrants.In 2012, the number of PLWHA was higher compared to 2007, while the proportion of undiagnosed HIV was lower, especially among MSM. Higher HIV testing rates, earlier treatment, and an improved life expectancy may explain these differences. HIV interventions need to be expanded in all key populations at higher risk, with special focus on migrants and key populationsliving outside of Amsterdam.